The Implementation of Activity Based Costing to Determine Cost of Service Sold (Case Study at X Guesthouse Malang) - Harfina Aulya Astrini; Helmy Adam (Jurnal Ilmiah Mahasiswa FEB, 2015)
Rates are the main financing models in service companies like Guesthouse or hotel. Determination of tariffs service becomes a fundamental decision. The huge costs to be one factor in determining the tariff for rooms, food and beverages and meeting packages at UB Guesthouse. This research is descriptive case study design and data analysis using quantitative descriptive analysis. The unit of analysis in this study is the UB Guesthouse Malang. The purpose of this study was to compare the results of calculations using the Activity Based Costing with prices from management. Therefore, the results of calculation of the room rate, food and beverages and meeting packages Activity Based Costing system have significant differences. The conclusion  is the differentiation is using activity based costing get the accurate cost and efficiency cost, so management can arrange the strategies to improve the profit.   Keywords: Activity Based Costing, COGS, Cost Driver, hotel